Perancangan Sistem Informasi Penyewaan Jasa Pelaminan Menggunakan Bahasa Pemprograman Php Dan Database Mysql - Rani Permata Adi; Firdaus (Journal of Computer Scine and Information Technology, 2021)
Silvia Wedding is a party equipment and music rental business in Pariaman City. The business has been operating for approximately 10 years and offers a variety of services, including Minang traditional wedding stage rentals, event decorations, photography, video shooting, catering, dance services, makeup, and music services. In managing rental and reservation transactions, Silvia Wedding still uses a manual system, recording customer data, party equipment rentals, and music reservations in a ledger. This system creates various problems, such as the risk of recording errors, data loss, and delays in obtaining information regarding the availability of party equipment according to customer schedules. To address these issues, the application of information technology is necessary through the development of a computer-based information system for party equipment rentals and music reservations. This information system is designed to facilitate more effective and efficient transaction management, facilitate owner access to asset availability information, and generate transaction reports quickly and accurately. With this information system, Silvia Wedding is expected to streamline business processes and improve the quality of service to customers.